2013
DOI: 10.1001/jamapediatrics.2013.780
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Early Exposure to Intimate Partner Violence and Parental Depression With Subsequent Mental Health Outcomes

Abstract: Objective To examine the association between parent reports of intimate partner violence (IPV) and depressive symptoms within the first 3 years of a child’s life with subsequent mental health conditions and psychotropic drug treatment. Design Prospective cohort study linking parental IPV and depression with subsequent billing and pharmacy data. Setting 4 pediatric clinics between November 2004 and June 2012 Patients/Participants 2,422 children Main Exposure Any report of IPV and/or parental depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 61 publications
4
48
1
2
Order By: Relevance
“…Given the case-control design, all analyses controlled for offspring ADHD and ODD diagnostic status at Wave 1. Furthermore, given the high comorbidity between parent ADHD and depression symptoms, as well as the association between parent depression and child ADHD (Bauer et al, 2013), we controlled for parent depression to improve the specificity of the putative association of parent ADHD symptoms with child outcome. Parameter estimates and 95% bias-corrected and accelerated confidence intervals for total and specific indirect effects were generated based on 1,000 bootstrap resamples (Preacher & Hayes, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the case-control design, all analyses controlled for offspring ADHD and ODD diagnostic status at Wave 1. Furthermore, given the high comorbidity between parent ADHD and depression symptoms, as well as the association between parent depression and child ADHD (Bauer et al, 2013), we controlled for parent depression to improve the specificity of the putative association of parent ADHD symptoms with child outcome. Parameter estimates and 95% bias-corrected and accelerated confidence intervals for total and specific indirect effects were generated based on 1,000 bootstrap resamples (Preacher & Hayes, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to ADHD, parent depression robustly predicts negative parenting and offspring psychopathology (Gau & Chang, 2013; P. Lee et al, 2013; Mars et al, 2012). In one study, parents reporting elevated depression were four times more likely to have a preschool child with ADHD than nondepressed parents (Bauer, Gilbert, Carroll, & Downs, 2013). Despite the frequent co-occurrence of parent ADHD and depression, as well as evidence that comorbid parent psychopathology is particularly predictive of offspring psychopathology (Loeber et al, 2009; Sellers, Collinshaw, et al, 2013), there is relatively little knowledge about the intergenerational continuity of ADHD in the context of co-occurring parent depression.…”
Section: Parenting Behavior As a Mediatormentioning
confidence: 99%
“…Estimates of poor parental mental health in general pediatric primary care clinics vary by problem. For example, studies have shown that 23-29 % of mothers screen positive for clinically significant depressive symptoms (Bauer et al 2013;Olson et al 2005) and approximately 6 % meet diagnostic criteria for post-traumatic stress disorder (Chemtob et al 2013). Poor parental mental health negatively affects child wellbeing and family functioning (e.g., Barrett et al 1996;Burke 2003;Chemtob et al 2013;Downey and Coyne 1990;Garber et al 2009;Gershoff et al 2003;Hammen et al 2004;Malia 2007;Patterson and Cobb 1971;Patterson 1982;Riley et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Exposure to parental depression concurrent with IPV has been associated with poor school functioning 17 and behavioral problems. 18 Exposure to parental anxiety, which frequently co-occurs with depression, 19,20 has also been associated with increased risk of behavioral problems. 21 This study examines the relationship between parental report of IPV and/or parental psychological distress (PPD), such as anxiety or depression, and the attainment of developmental milestones within the first 6 years (72 months) of a child' s life.…”
mentioning
confidence: 99%